Brine Shrimp Lethality of Atuna racemosa Raf. (Chrysobalanaceae) Fruits Extracted with Varying Acetic Acid Concentrations - Ang, Aileen May Gabule; Reyes, Fritzie Gay Embrado (Asian Journal of Biological and Life Sciences, 2019)
Introduction:A racemosa,commonly known as “Tabon-tabon” in the Philippines, is found to be native to some parts of Northern Mindanao and has been known for its ethnomedicinal uses.Objectives:In this study, preliminary investigation on the cytotoxic activity, i.e. brine shrimp lethality, of the fruit extracted with a safer solvent such as acetic acid was conducted.Materials and Methods:Extraction ofAtuna racemosaRaf. halved fruits was carried out using 1, 3 and 5% aqueous acetic acid. The cytotoxic properties of the aqueous acetic acid extracts were determined using Brine Shrimp Lethality Assay (BSLA).Results and Discussion:Alkaloids, anthraquinones, flavonoids, phenols and saponins were all detected in the 1%, 3% and 5% acetic acid extracts ofA. racemosafruits. Percent mortality of brine shrimp nauplii is an indication of the cytotoxic effects of the aqueous acetic acid fruit extracts ofA. racemosa.The percentage mortality of the nauplii is directly proportional to the concentration of the extracting solvent. Percent mortality of the brine shrimp nauplii exposed to 5% aqueous acetic acid extract was statistically higher as compared to that of 1 and 3%. The concentration of the acetic acid may have influenced the extractability of cytotoxic compounds from the fruits ofA. racemosa.Conclusion:The present findings imply that the aqueous acetic acid extracts ofA. racemosafruits were cytotoxic against brine shrimp nauplii. This property may be accounted to the detected phytochemicals in the extracts.
Keywords: A. racemosa fruit; Acetic acid; Brine shrimp lethality